Exploring the active ingredients and pharmacological mechanisms of the oral intake formula Huoxiang Suling Shuanghua Decoction on influenza virus type A based on network pharmacology and experimental exploration - Tang, Ruying; Wang, Linyuan; Zhang, Jianjun; Li, Xinyu; Tan, Lingyun; He, Wei; Han, Hui; Liu, Yuan; Wang, Keyu; Wang, Mengyao (Frontiers in Microbiology, 2022)
Objective To investigate the active ingredients, underlying anti-influenza virus effects, and mechanisms of Huoxiang Suling Shuanghua Decoction (HSSD). Materials and methods The therapeutic effect of HSSD were confirmed through the survival rate experiment of H1N1-infected mice. Then, the HSSD solution and the ingredients absorbed into the blood after treatment with HSSD in rats were identified by UPLC/Q-TOF MS, while the main contents of ingredients were detected by high performance liquid chromatography (HPLC). Next, a systems pharmacology approach incorporating target prediction, gene ontology (GO) enrichment, kyoto encyclopedia of genes and genomes (KEGG) pathway analysis, and molecular docking were performed to screen out the active compounds and critical pathways of HSSD in treating influenza. According to prediction results, real-time quantitative polymerase chain reaction (RT-qPCR) and immunohistochemistry assay were used to detect the mRNA and protein expression levels of critical targets in H1N1-infected mice lungs. Results Huoxiang Suling Shuanghua Decoction improved the survival rate of H1N1-infected mice and prolonged the mice’s lifespan. Besides, HSSD exerts an antivirus effect by decreasing the levels of hemagglutinin (HA) and nucleoprotein (NP) to inhibit the replication and proliferation of H1N1, reducing the lung pathological state, inhibiting the cell apoptosis in the lung, and regulating the abnormal responses of peripheral blood, including GRA, LYM, white blood cell (WBC), PLT, and hemoglobin (HGB). Then, 87 compounds in the HSSD solution and 20 ingredients absorbed into the blood after treatment with HSSD were identified. Based on this, combined with the network analysis and previous research on antivirus, 16 compounds were screened out as the active components. Moreover, 16 potential targets were predicted by network pharmacology analysis. Next, molecular docking results showed stable binding modes between compounds and targets. Furthermore, experimental validation results indicated that HSSD regulates the contents of Immunoglobulin A (IgA), Immunoglobulin M (IgM), and Immunoglobulin G (IgG) in serum, modulating the levels of IFN-γ, IL-6, IL-10, MCP-1, MIP-1α, and IP-10 in the lung tissue, and significantly decreasing the mRNA and protein expressions of TLR4, CD14, MyD88, NF-κB p65, HIF1 α, VEGF, IL17A, and IL6 in the lung tissue. Conclusion Huoxiang Suling Shuanghua Decoction exerts an anti-influenza effect by affecting the expressions of mRNA and protein including TLR4, CD14, MyD88, NF-kB p65, HIF-1α, VEGF, IL17A, IL6, and inhibiting the accumulation of inflammation. Our study provided experimental pieces of evidence about the practical application of HSSD in treating influenza.